Produção de mudas de três espécies ornamentais sob irrigação com águas salinas - Bezerra, Francisco Mardones Servulo (2019)
Climate change and its impacts, especially in arid and semi-arid regions, point to a worsening of the crisis in access to quality water for consumption and food production. In this context, it is necessary to rethink or advance in the design of techniques and technologies that allow the use of marginal waters, including brackish and saline waters, making water of superior quality available for supply. The Brazilian Northeast, historically characterized as dry, occupies a prominent place in the national flower production scenario, being the third largest producer of ornamental plants in Brazil. The cultivation of flowers in the Northeast demands a considerable volume of water, since its production is irrigated. Given the large number of ornamental species, scattered in the most diverse environments, a large part of these may show tolerance to salinity, representing a concrete possibility of using saline water in their cultivation. However, studies in this area, with ornamental species, are more commonly focused on the post-establishment stage of culture in the field or of these in adulthood. Given the context, the objective was to analyze the responses of three ornamental species to irrigation with saline water in the seedling production phase and classify them according to salinity tolerance. The research was conducted in a protected environment, from July to September 2018. The design used was in randomized blocks, arranged in a 3 x 10 factorial scheme, referring to the three ornamental species (Celosia argentea, Tagetes patula and Catharanthus roseus) and ten levels of electrical conductivity of irrigation water ECw (0.5; 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 5.0 and 6.0 dS m-1). The salinity tolerance in the production phase of Catharanthus roseus, Tagetes patula and Celosia argentea seedlings was studied, considering four classification methods, compared based on the values of relative reductions in biometric and qualitative data. The implications of saline stress on physiological and biometric variables were also analyzed. The different classification methods show a greater sensitivity to the salinity of C. roseus in relation to the species T. patula and C. argentea in this order. In addition to what was observed less negative effect of salt stress on physiological and biometric variables of the species C. argentea, followed by T. patula and C. roseus.